Respostas
respondido por:
1
Esta bem explicado basta seguir que chegara ao resultado, bons estudos
(4a-5b)² - 2(8a²+12b²) =
= (4a-5b).(4a-5b) + (-16a² - 24b²) =
= 16a² - 20ab - 20ab + 25b² - 16a² - 24b² =
= b²-40ab
Espero ter ajudado, bons estudos.
(4a-5b)² - 2(8a²+12b²) =
= (4a-5b).(4a-5b) + (-16a² - 24b²) =
= 16a² - 20ab - 20ab + 25b² - 16a² - 24b² =
= b²-40ab
Espero ter ajudado, bons estudos.
Perguntas similares
7 anos atrás
7 anos atrás
7 anos atrás
10 anos atrás
10 anos atrás
10 anos atrás
10 anos atrás